ANALYSIS OF INTERACTION PATTERNS IN SECONDARY SCHOOL ECONOMICS CLASSROOMS IN KWARA STATE, NIGERIA (Unilorin Journal of Lifelong Education, 2023)
The descriptive research design of the observational type was adopted for this study. A sample of 10 Economics classes from five LGAs of 16 in Kwara State, were purposely selected for observation, a total of 219 students during each classroom lesson observed twice. Flander's Interaction Analysis Category System (FIACS) was used to observe interactions in the classes. The data gathered were analyzed with percentages and charts. The study found that 86% of classroom interaction was teacher-talk, 95% verbal interaction, 62% interaction pattern of the non-numerate classroom, while activity in Economics classes was mostly academic (83%) in Kwara State; all teacher-centred. It was recommended that that teaching technique should be more learner-cantered.